A multi‐institutional validation study of prognostic nomograms for retroperitoneal sarcoma. Issue 5 (13th July 2021) - Squires, Malcolm H.; Ethun, Cecilia G.; Donahue, Erin E.; Benbow, Jennifer H.; Anderson, Colin J.; Jagosky, Megan H.; Salo, Jonathan C.; Hill, Joshua S.; Ahrens, William; Prabhu, Roshan S.; Livingston, Michael B.; Gower, Nicole L.; et al.
Abstract: Background and Objectives: Prognostic nomograms for patients undergoing resection of retroperitoneal sarcoma (RPS) include the Sarculator and Memorial Sloan Kettering (MSK) sarcoma nomograms. We sought to validate the Sarculator and MSK nomograms within a large, modern multi‐institutional cohort of patients with primary RPS undergoing resection. Methods: Patients who underwent resection of primary RPS between 2000 and 2017 across nine high‐volume US institutions were identified. Predicted 7‐year disease‐free (DFS) and overall survival (OS) and 4‐, 8‐, and 12‐year disease‐specific survival (DSS) were calculated from the Sarculator and MSK nomograms, respectively. Nomogram‐predicted survival probabilities were stratified in quintiles and compared in calibration plots to observed survival outcomes assessed by Kaplan–Meier estimates. Discriminative ability of nomograms was quantified by Harrell's concordance index (C‐index). Results: Five hundred and two patients underwent resection of primary RPS. Histologies included leiomyosarcoma (30%), dedifferentiated liposarcoma (23%), and well‐differentiated liposarcoma (15%). Median tumor size was 14.0 cm (interquartile range [IQR], 8.5–21.0 cm). Tumor grade distribution was: Grade 1 (27%), Grade 2 (17%), and Grade 3 (56%). Median DFS was 31.5 months; 7‐year DFS was 29%. Median OS was 93.8 months; 7‐year OS was 51%. C‐indices for 7‐year DFS, and OS by the Sarculator nomogram were 0.65 (95% confidence interval [CI]: 0.62–0.69) and 0.69 (95%CI: 0.65–0.73); plots demonstrated good calibration for predicting 7‐year outcomes. The C‐index for 4‐, 8‐, and 12‐year DSS by the MSK nomogram was 0.71 (95%CI: 0.67–0.75); plots demonstrated similarly good calibration ability. Conclusions: In a diverse, modern validation cohort of patients with resected primary RPS, both Sarculator and MSK nomograms demonstrated good prognostic ability, supporting their ongoing adoption into clinical practice.